Visual Identity as a Visual Representation Media in Branding Bakso Atok - Indrajaya, Grandy; Redintan, Muhammad Justin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
Designing a visual identity is very important because it is an effort to represent and represent a particular brand or brands. Apart from representing the brand, visual identity can also increase consumers' sense of awareness in choosing the brand. This research is interesting in raising the problem of street vendors, namely